(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
With internet of things (IoT) technologies modern agriculture has significantly enhanced its farming efficiency and sustainability. This review explores advancements in IoT-enabled farm machinery and their role in promoting sustainable water management practices. IoT-based solutions, such as smart irrigation systems, autonomous equipment, and livestock monitoring tools, enable precise resource allocation, reducing water waste by up to 50% compared to traditional methods. These technologies facilitate real-time data collection and analysis, allowing farmers to optimize irrigation schedules, monitor water quality, and implement rainwater harvesting systems effectively. Studies show that precision agriculture techniques can improve water use efficiency by 20-30%, while IoT-enabled water quality monitoring reduces crop losses due to contamination by 15-25%. Despite their potential, challenges such as high costs, technical expertise requirements, and connectivity issues hinder widespread adoption. Future prospects include the integration of artificial intelligence, development of low-cost solutions, and policy support to overcome these barriers. By addressing global water scarcity and improving agricultural productivity, IoT-enabled innovations are paving the way for a more sustainable and resilient farming sector, crucial for ensuring food security in the face of climate change and population growth.